The Influence of Environmental, Social, and Governance (ESG) Factors on Tobin’s Q in the Banking Sector Companies in Southeast Asia - Safitri, Winda (UNIB Press, 2025)
This study aims to analyze the effect of Environmental, Social, and Governance (ESG) factors on Tobin's Q value in banking sector companies listed on the Stock Exchange in Southeast Asia. Using panel data from 21 banks over the period 2013 to 2022, this study found that social factors have a positive and significant influence on Tobin's Q, while environmental and governance factors do not show a significant influence. These results show the importance of companies to pay attention to social aspects in their ESG implementation to increase firm value.